PENGETAHUAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) TERHADAP SIKAP DAN PERILAKU PADA REMAJA PUTRI - Linda Juwita (Adi Husada Nursing Journal, 2019)
ABSTRACT Women's knowledge of the risks and benefits of early detection of breast cancer positively affects the beliefs about health, attitudes, and behavior. This study was using correlational research design with cross sectional approach. The population were all female students of Faculty of Nursing of Widya Mandala Catholic University Surabaya (UKWMS). Samples of this study was 134 people. Variable independent in this research that is knowledge, and variable dependent in this research that is attitude and action of Breast self-examination (BSE). Spearman Correlation test statistic showed that there is corelation between knowledge and attitude toward BSE with a signficance value p = 0,009, while between knowledge and action of BSE a signficance value p = 0,607. There was weak significant corelation identified between knowledge of breast self-examination (BSE) and attitude toward BSE. There was no relationship between knowledge and action of BSE. Attitude toward BSE will be influenced education, environment and experience. action of BSE is influenced by the process to shape the behavior. Keywords: Knowledge, Attitude, Action, Breast self-examination (BSE)